Re-description of some poorly known species of the family Syllidae (Annelida) - Verdes, Aida; Aguado, M. Teresa; San Martín, Guillermo (Journal of the Marine Biological Association of the United Kingdom, 2013)
Several poorly known species of the family Syllidae (Annelida) have been revised and re-described. New diagnosis and taxonomic remarks are provided for Erinaceusyllis erinaceus, Opisthosyllis neglecta comb. nov., Parapionosyllis parapionosylliformis [sic for paraprionosylliiformis] comb. nov., Prosphaerosyllis semiverrucosa comb. nov. and Amblyosyllis granosa.
World Polychaeta Database (WPolyDb)